A new species of planthopper in the genus Jamaha (Hemiptera: Fulgoroidea: Nogodinidae) from the Northeastern coast of Jamaica - Bahder, Brian W.; Myrie, Wayne; Helmick, Ericka E.; Dam, Alex R. Van; Bartlett, Charles R. (Zootaxa, 2023)
A new species of Jamaha Gnezdilov & O’Brien, 2008, is described from Jamaica and compared with other species in the genus. A key to the species of Jamaha is provided. Molecular data for the five-prime region of the cytochrome c oxidase subunit I (COI) gene and 18S rRNA gene is provided and compared to available Colpopterini, with other Nogodinidae as the outgroup, for a preliminary phylogenetic analysis. While the Colpopterini grouped with high support, these data remain too sparse to draw firm conclusions.